THE IMPORTANCE OF STEAM EDUCATION IN ENSURING THE WORTHY PARTICIPATION OF NEW UZBEKISTAN’S YOUTH IN THE GLOBAL SCIENTIFIC SPACE (SCIENCE TIME JOURNAL, 2026)
The rapid transformation of the global economy, driven by digitalization, artificial intelligence, and technological innovation, demands a new generation of highly skilled and creative specialists. As Uzbekistan progresses toward building a modern, knowledge-based society, the role of young people becomes increasingly central. This paper explores the importance of STEAM (Science, Technology, Engineering, Arts, and Mathematics) education in empowering the youth of New Uzbekistan to become competitive participants in the international scientific arena. The study analyzes global trends, national reforms, and the pedagogical advantages of STEAM education, offering recommendations for strengthening Uzbekistan’s position in global science and innovation.